Anisakidae and Raphidascarididae larvae parasitizing Selene setapinnis (Mitchill, 1815) in the State of Rio de Janeiro, Brazil - Fontenelle,Gabrielle (2015)
Between February and August, 2012, thirty specimens of Atlantic moonfish, Selene setapinnis, were purchased in local markets in Niterói, State of Rio de Janeiro, Brazil, with the aim of analyzing the presence of anisakid nematodes, establishing their rates of parasitism and infection sites, due to importance in the sanitary inspection. A total of sixty nematode larvae, belonging to at least two species were found: nine larvae of Terranova sp., Anisakidae, with prevalence (P) of 13.3%, mean intensity (MI) of 2.25, mean abundance (MA) of 0.30 and range of infection intensity (RI) from 1 to 6; and 51 larvae of Hysterothylaciumfortalezae, Raphidascarididae, with P = 26.7%, MI = 6.40, MA = 1.70, and RI = 1-17. The infection sites for Terranova sp. were the mesentery and liver serosa; and for H. fortalezae, the infection sites were the mesentery, abdominal cavity and liver serosa. New morphological data from scanning electron microscopy, on the external structures of H. fortalezae (mainly at the posterior end), are presented. This is the first report of H. fortalezae parasitizing S. setapinnis.